A NOVEL MODEL FOR ORIENTATION OF LINEAR OPTICAL SATELLITE IMAGES BASED IN THE ADAPTATION OF THE ORBIT-ATTITUDE MODEL - Rodrigues, Tiago Lima; Machado, Marcela do Valle [UNESP] (Univ Federal Parana, Centro Politecnico, 2019)
In this paper a novel model to orient a pushbroom linear optical satellite image is proposed. This one is based in the adaptation of the Orbit-Attitude model for use of the Modified UCL Kepler platform model. It has only the components of satellite position and velocity as unknowns. This implies not only the reduction of unknowns but also the elimination of initial adjustments of the orbit to estimate the polynomial parameters. In order to validate the model, four experiments were conducted using one HRC-CBERS 2B image. Two distributions of ground controls points (GCPs) were tested, 70 and 35 GCPs. A quantity of 43 check points (CPs) was used to analyze the planimetric accuracies of the orientations. For comparisons purpose the image was also oriented with platform model using 2nd order polynomial. The results showed that the planimetric accuracy difference in the use of the two models is 4 and 6 centimeters in the two mentioned configurations of GCPs, respectively. However, the main advantage of applying the proposed model is the direct use of ephemeris without the necessity of interpolations and preadjustments, which makes the orientation process simpler.
Keywords: Linear optical satellite image; Orbit-Attitude Model; UCL Kepler platform model